Optimizing Replenishment System in Refrigerated Beverage Supply Chain Using Control Charts and TOPSIS: A Case Study of Convenience Stores in Taiwan - Hsu, Ya-Chen; Chang, Ting-Yu; Chen, Yan-Kwang (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
As consumers become more health-conscious, the demand for fresh, short-shelf-life beverages has increased, making effective inventory management essential. This study optimizes a replenishment system for refrigerated beverages in convenience stores to ensure product freshness, reduce waste, and improve inventory efficiency. To achieve this goal, we used X̅ control charts and modified Western Electric rules to monitor demand and inventory dynamics, enabling accurate forecasting and responsive supply chain management. System performance, evaluated based on inventory stability, bullwhip effect, and service level, was integrated using the technique for order preference by similarity to ideal solution (TOPSIS) to determine the optimal replenishment parameter combination from historical data. This study proposes an SPC-based replenishment framework that not only applies control charts to monitor demand and inventory data but also leverages TOPSIS to optimize key performance indicators. This integrated approach balances methodological rigor with practical applicability, enabling timely, data-driven decisions and enhancing supply chain performance for refrigerated beverages.